Oral myeloid cells uptake allergoids coupled to mannan driving Th1/Treg responses upon sublingual delivery in mice. Issue 4 (31st January 2018) - Soria, I.; López‐Relaño, J.; Viñuela, M.; Tudela, J.‐I.; Angelina, A.; Benito‐Villalvilla, C.; Díez‐Rivero, C. M.; Cases, B.; Manzano, A. I.; Fernández‐Caldas, E.; Casanovas, M.; Palomares, O.; et al.
Abstract: Background: Polymerized allergoids coupled to nonoxidized mannan (PM‐allergoids) may represent novel vaccines targeting dendritic cells (DCs). PM‐allergoids are better captured by DCs than native allergens and favor Th1/Treg cell responses upon subcutaneous injection. Herein we have studied in mice the in vivo immunogenicity of PM‐allergoids administered sublingually in comparison with native allergens. Methods: Three immunization protocols (4‐8 weeks long) were used in Balb/c mice. Serum antibody levels were tested by ELISA. Cell responses (proliferation, cytokines, and Tregs) were assayed by flow cytometry in spleen and lymph nodes (LNs). Allergen uptake was measured by flow cytometry in myeloid sublingual cells. Results: A quick antibody response and higher IgG2a/IgE ratio were observed with PM‐allergoids. Moreover, stronger specific proliferative responses were seen in both submandibular LNs and spleen cells assayed in vitro. This was accompanied by a higher IFNγ/IL‐4 ratio with a quick IL‐10 production by submandibular LN cells. An increase in CD4 + CD25 high FOXP3 + Treg cells was detected in LNs and spleen of mice treated with PM‐allergoids. These allergoids were better captured than native allergens by antigen‐presenting (CD45 + MHC‐II + ) cells obtained from the sublingual mucosa, including DCs (CD11b + ) and macrophages (CD64 + ). Importantly, all the differential effects induced by PM‐allergoids were abolished when using oxidized instead of nonoxidized PM‐allergoids. Conclusion: Our results demonstrate for the first time that PM‐allergoids administered through the sublingual route promote the generation of Th1 and FOXP3 + Treg cells in a greater extent than native allergens by mechanisms that might well involve their better uptake by oral antigen‐presenting cells.